Studi Moderasi Berita Pada Pengaruh Efek Disposisi Terhadap Sentimen Investor yang di Moderasi Kembali Oleh Tingkat Kesepakatan Investor Pasar Modal di Indonesia - Putri Fariska, - (2021)
Investors assume that the news or information obtained is accurate so that every investment decision taken tends to produce a bias. This deviation or bias shows that investors are not completely rational, where an investor does not only use his common sense in making investment decisions but is very likely to be influenced by the emotions felt at that time. Behavior finance is an area of research that refutes the efficient market hypothesis theory that has developed over the last three decades that assume that investors are rational. Investor sentiment is one of the research areas in behavioral finance theory that analyzes investor behavior and how it affects stock market activity. With the advancement of information technology in recent years, the trend of using social media has greatly increased in all circles, including investors who are actively seeking news or information and also investment advice given by expert investors. The ease and disclosure of such information lead to greater deviations or biases in investment decisions and also in the way investors form a belief or sentiment. Twitter is a social media platform that is designed as a forum for sharing information, tweets, or ideas between investors, traders, and expert. For this reason, quantifying investor sentiment can be investigated through microblogs tweets using social media data mining methods for the analysis of public sentiment. So, in this research, a study of news moderation and investor agreement level on the effect of disposition effect bias on investor sentiment in the capital market in Indonesia is conducted. This research using data from investors who are active on the twitter platform based on daily tweets with the hashtag symbol 60 company shares listed on the Indonesian stock exchange in the period January 2015 - May 2020 with 10,533 data and 558 users. With the Regression test approach moderated moderation analysis, the results of this study are that underreaction or overreaction to news of stock price changes and negative news moderates the effect of the disposition effect on investor sentiment where the magnitude of the effect will depend on the level of investor agreement. Disposition effect, level agreement of investors, monetary news, and information quality from investors alpha have a conditional effect on investor sentiment. Meanwhile, the conditional interaction between the moderating variable and the disposition effect simultaneously influences investor sentiment, except for its relationship with negative news.